2019
DOI: 10.15517/rbt.v67i2supl.37208
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of common bean (Phaseolus vulgaris) var. Brunca

Abstract: Common bean is a crop recalcitrant to in vitro regeneration and therefore it lacks an efficient transformation protocol that can be reproduced using A. tumefaciens. The main goal of this study was to establish a protocol for A. tumefaciens mediated transformation of Phaseolus vulgaris var. Brunca by marker genes (gusA and nptII) together with the gene for trehalose-6-phosphate synthase from Saccharomyces cerevisiae (TPS1) used in other species to increase tolerance to abiotic stress. The β-glucuronidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The transformation frequency is a cultivar‐dependent trait (Mukeshimana et al, 2013 ). Agrobacterium‐mediated transformation and shoot regeneration through somatic embryogenesis has been successfully implemented recently but with low transformation frequencies (0.5%–2.5%) indicating that this technology is far from routine (Solís‐Ramos et al, 2019 ; Song et al, 2020 ).…”
Section: Genetic Resources and Biofortification Strategies For Common...mentioning
confidence: 99%
“…The transformation frequency is a cultivar‐dependent trait (Mukeshimana et al, 2013 ). Agrobacterium‐mediated transformation and shoot regeneration through somatic embryogenesis has been successfully implemented recently but with low transformation frequencies (0.5%–2.5%) indicating that this technology is far from routine (Solís‐Ramos et al, 2019 ; Song et al, 2020 ).…”
Section: Genetic Resources and Biofortification Strategies For Common...mentioning
confidence: 99%
“…Brunca, periodos de co-cultivo de tres a cuatro días, resultaron en una integración adecuada de los genes GUS o nptII (Solís-Ramos et al, 2019). En la presente investigación se demostró que para el cultivar 'ICA Pijao', tres días de co-cultivo reducen las afectaciones en la regeneración de brotes en un 10 %.…”
Section: Tiempo De Infiltración Por Vacíounclassified
“…The preliminary results laid the foundation of this research. Because recalcitrance of common bean genotypes to in vitro regeneration from non-meristem containing tissues is the primary limitation for stable transformation [16,25,26], the preculture method described for the Olathe' pinto bean may facilitate transformation of the other common bean cultivars. In fact, it has been reported that the EHA105-mediated transformation of primary and proliferative calli of common bean cv.…”
Section: Meristem Tissues Are a Reliable Source Of Regenerable Callimentioning
confidence: 99%
“…An efficient and reproducible transformation system for the production of stable transgenic common bean plants is still lacking. The primary limitation has been recalcitrance of common bean genotypes to in vitro regeneration from non-meristem containing tissues [16,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation